Is the prevalence of equinus foot in cerebral palsy overestimated?: results from a meta-analysis of 4814 feet - Horsch, Axel; Klotz, Matthias C. M.; Platzer, Hadrian; Seide, Svenja; Zeaiter, Nancy; Ghandour, Maher (Journal of Clinical Medicine, 2021)
Background: Equinus is a common foot deformity in patients with cerebral palsy (CP). However, its prevalence is scarcely reported in the literature. Therefore, we conducted this review to estimate the prevalence of equinus foot in CP. Methods: Eight databases were searched. Our primary outcome was the prevalence of equinus foot in CP patients. Subgroup analysis was conducted based on study design, the laterality of CP, and whether equinus foot was defined or not. Results: The prevalence of equinus foot in CP was 93% (95% CI: 71-99). The prevalence was 99% (95% CI: 55-100), 96% (95% CI: 57-100), and 65% (95% CI: 37-86) in unilateral, both, and bilateral CP, respectively. Based on study design, equinus foot prevalence was 92% (95% CI: 34-100) in case series and 62% (95% CI: 47-74) in cohort studies. Four studies reported definition criteria for equinus foot, with a pooled prevalence rate of equinus foot of 99% (95% CI: 36-100) compared to a rate of 89% (95% CI: 59-98) among studies that lacked a definition criterion. Conclusions: This is the first meta-analysis to address the prevalence of equinus foot in CP patients. Although its prevalence is very high, our findings should be interpreted with caution due to the presence of multiple limitations, such as the lack of standardized definition criteria for equinus foot, the inappropriate study design, the wide confidence interval of equinus foot rate, and the small number of studies investigating it as a primary outcome.
Gesehen am 02.12.2021